How Does the Influence of Moral Values Affect Children's Use of Roblox in Character Education? - Damanhuri; Wali, Muhammad (International Journal Education and Computer Studies (IJECS), 2024)
This experimental study evaluated the effectiveness of Roblox game design based on local Indonesian values in strengthening character education for children aged 9-12 years through a mixed-methods approach. Involving 320 participants from 15 schools in Aceh Province, this study measured behavioral changes using the Moral Competence Game Scale (MCGS-α=0.87) and analyzed 1,250 transcripts of game interactions over a 12-week period. Quantitative results showed a significant increase in prosocial behavior (42%, p<0.01) and conflict resolution competence (d=0.63), while qualitative analysis revealed the dominance of collaborative communication patterns (78%) in the avatar rescue scenario. The integration of local wisdom such as mutual cooperation simulations in shared resource management mechanics, adaptation of local Acehnese games, and deliberation-based narratives were shown to increase the retention of justice values by 28% compared to generic content. The main challenges included exposure to 23% of morally ambiguous content and technostress in 65% of parents, which were addressed through the Onion-Layer Protection model combined with AI moderation and community reporting. The research implications resulted in Ethical Design Guidelines for local game developers that include technical parameters such as 30% memory usage optimization with 1:1 trim sheet technique and 15% FPS increase through adaptive LOD system.